2004
DOI: 10.1111/j.1365-2044.2004.03832.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spinal anaesthesia and obesity on maternal respiratory function during elective Caesarean section*

Abstract: SummarySpinal anaesthesia for Caesarean section has gained widespread acceptance. We assessed the impact of spinal anaesthesia and body mass index (BMI) on spirometric performance. In this prospective study, we consecutively assessed 71 consenting parturients receiving spinal anaesthesia with hyperbaric bupivacaine and fentanyl for elective Caesarean section. We performed spirometry during the antepartum visit (baseline), immediately after spinal anaesthesia, 10-20 min, 1 h, 2 h after the operation, and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 26 publications
(53 reference statements)
3
36
1
2
Order By: Relevance
“…This is consistent with observations made in parturients receiving spinal anaesthesia for elective Caesarean section [10].…”
Section: Effect Of Obesitysupporting
confidence: 92%
“…This is consistent with observations made in parturients receiving spinal anaesthesia for elective Caesarean section [10].…”
Section: Effect Of Obesitysupporting
confidence: 92%
“…In a cohort of patients with prolonged desaturations, Taenzer et al found that manual recordings of SpO 2 were higher than those recorded by the automated system by 6.5% on average, and did not reflect physiologic patient state when compared with continuous automated sampling (22). However, at the time of our study, such automated continuous monitoring of SpO 2 was not yet available at our obstetric operating theatre.…”
Section: Discussionmentioning
confidence: 47%
“…It can be envisaged that spinal anaesthesia in an obese patient may contribute to further deterioration of respiratory function (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations